The Importance of Ethics and Social Responsibility in International Business - Dara Citra Pratiwi (Journal of Management and Business Innovations, 2021)
Ethics is a person's beliefs about whether certain decisions, behaviors, or actions are right or wrong. Therefore, what determines ethical behavior differs from one person to another. For example, someone who finds money on the floor of an empty house may believe it is magnificent to pick it up, while another may feel obligated to return it to the lost items section. The concept of ethical behavior usually refers to behavior that is accepted by general social norms. Unethical behavior is behavior that does not follow general social norms. Ethical behavior in business is essential for the survival of the business itself. Businesses that do not have ethical behavior will be detrimental to the business itself, especially from a long-term perspective. A healthy business is not only a profitable business but a healthy and promising business that, in addition to being a profitable business, is also a morally good business with a sense of responsibility that can be implemented.Keywords: Business ethics, social responsibility, international business